Approaching Entangled Moral Attitudes. (August 2016) - Bale, Kjersti
Abstract : Substantive readings of literary works are central to Martha C. Nussbaum's attempt to develop a conception of morality based on particular instances. Building on her key concepts perception and improvisation while adjusting them by way of drawing on works by Cora Diamond, this article suggests that not only literature, but also what W. T. A. Mitchell has coined "imagetexts" display a wide range of values and attitudes that question abstract moral principles. By inviting readers and viewers to compare and contrast their cognitive as well as emotional responses, text and image spur a kind of moral thinking oriented towards the particular. A salient incident from Joseph Conrad's novella Heart of Darkness (1902) and Liv Bugge's art book You Make Me Want to Die in the Countryside: A Meditation on "Heart of Darkness" by Joseph Conrad (2011) provide test cases for this assertion. Diverging and incompatible moral attitudes are dispersed and explored throughout these works and the orchestration of diverse attitudes calls for equally diverse cognitive and emotional responses.